African women in search of global identity: An exploration of feminism and Afropolitanism in Chimamanda Adichie’s works - Eke, Gloria Ori; Njoku, Anthony (Journal of Gender and Power, 2020)
Many variants of feminism have been branded over time and that has given feminism a multiple identity. One of the new revelations of feminism in recent times is “Afropolitan Feminism”, a branch of African feminism conceived in this research to deal with the story of African women in the homeland and the Diaspora trying to assume the status of world citizens (Metropolites) to de-emphasize their origins. What is the nature of Afropolitan Feminism? What is the link between Feminism and Afropolitanism? To what extent do Adichie’s characters show the attributes of Afropolitans? This paper illuminates the concepts of feminism and Afropolitanism and the latter’s traits in Adichie’s characters in Americanah and The Thing Around Your Neck. It deals with Diaspora issues and the way African women in literary fictions try to stem the effects of global maladies like African patriarchy, Western racism and sexism. The paper further discusses social awareness and feminist tendencies displayed by the characters. It ends by noting that feminism which assumes the dimension of Afropolitanism in Adichie’s works is a becoming trend rather than a fixed norm.